2016
DOI: 10.1002/lsm.22506
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into localized re‐treatment of the retina with a 3‐nanosecond laser

Abstract: The overall results provide a measure of confidence that re-treatment of patients with 2RT should not provide any additional risk of developing visual scotomas, choroidal neovascularizations, or inflammatory events. Indeed, the collated results indicate that the metabolic and structural disruption to the RPE-retina caused by short pulse duration laser treatment is resolved within a short time frame such that re-treatment elicits a phenotype indistinguishable from single treatment. Lasers Surg. Med. 48:602-615,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
2
13
0
1
Order By: Relevance
“…These new cells retile over the laser region, theoretically rejuvenating the RPE with new ''younger'' RPE cells in these areas. 23,24,29 The results of the current study are consistent with these previous findings. At 5 hours after subthreshold laser, flat mount labeling with phalloidin, a high-affinity F-actin probe that labels RPE cell membranes, showed RPE cells were ablated.…”
Section: Effects Of Nanosecond Laser Treatment On the Rpe And Bruch'ssupporting
confidence: 83%
See 4 more Smart Citations
“…These new cells retile over the laser region, theoretically rejuvenating the RPE with new ''younger'' RPE cells in these areas. 23,24,29 The results of the current study are consistent with these previous findings. At 5 hours after subthreshold laser, flat mount labeling with phalloidin, a high-affinity F-actin probe that labels RPE cell membranes, showed RPE cells were ablated.…”
Section: Effects Of Nanosecond Laser Treatment On the Rpe And Bruch'ssupporting
confidence: 83%
“…In addition, no evidence of other abnormal vessel labeling within the retina was apparent. This finding is consistent with the work of Chidlow et al 23 who have shown histologically that at 7 days after nanosecond pulsed laser treatment, dark-agouti rats do not have vascular leakage or abnormal choroidal vessels even when a suprathreshold, high-energy treatment is used. We extended on this initial finding, showing that not only at 7 days, but also at 3 months, there is no histologic evidence of CNV in eyes treated with a clinically relevant laser dose (0.065 mJ).…”
Section: The Nanosecond Laser Does Not Induce Angiogenesis In Mice Evsupporting
confidence: 82%
See 3 more Smart Citations